2023
DOI: 10.1021/acsmaterialslett.3c00310
|View full text |Cite
|
Sign up to set email alerts
|

A Donor–Acceptor Cage for Thermally Activated Delayed Fluorescence: toward a New Kind of TADF Exciplex Emitters

Abstract: We present the rational design of an organic cage combining an electron-donating (D) triazatruxene and electron-accepting (A) triphenyl triazine connected by three electronically inert pillars. This controlled architecture leads to a precise spatial separation and cofacial alignment of the D and A motifs. Such an architecture induces an efficient intramolecular through-space charge transfer (TSCT), providing a small singlet−triplet energy difference (ΔE ST ) of 0.049 eV, and thus gives rise to a thermally acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…[14][15][16] Since their inception in 2009 from Cooper's group, 17 research on the design and synthesis of different linkages, shapes, topologies, sizes, and functions of POCs has attracted much attention from chemists and materials scientists. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Our group focuses on using concave-shaped calix [4]resorcinarene (C4RA) as synthons in construction of novel C4RA-based POCs and their applications. [34][35][36][37][38][39][40] In this work, we designed and synthesized two robust nitrogen-rich POCs aiming at efficient storage and separation of C 2 H 2 , as the basic nitrogen groups have been veried to have strong interaction with acidic C 2 H 2 gas.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Since their inception in 2009 from Cooper's group, 17 research on the design and synthesis of different linkages, shapes, topologies, sizes, and functions of POCs has attracted much attention from chemists and materials scientists. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Our group focuses on using concave-shaped calix [4]resorcinarene (C4RA) as synthons in construction of novel C4RA-based POCs and their applications. [34][35][36][37][38][39][40] In this work, we designed and synthesized two robust nitrogen-rich POCs aiming at efficient storage and separation of C 2 H 2 , as the basic nitrogen groups have been veried to have strong interaction with acidic C 2 H 2 gas.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] To design CP-TADF, both chirality for circularly polarized luminescence (CPL) and the prerequisite of the small energy difference between the lowest singlet (S 1 ) and triplet (T 1 ) excited states (DE ST ) for TADF 25 should be fulfilled. Ealier study 26 showed that organic cages composed of electron donor and acceptor moieties exhibit efficient TADF emission via intramolecular through-space charge transfer (TSCT). 27,28 By reasoning that molecular chirality and TSCT can be induced simultaneously by the spatial arrangement of achiral/prochiral donors and acceptors, we herein report the first example of an organic cage, denoted DA-2, that exhibits CP-TADF.…”
mentioning
confidence: 99%
“…In the last two decades, organic light-emitting diodes (OLEDs) have attracted great attentions owing to the use of the triplet excited-available emitters. As one promising type of these emitters, thermally activated delayed fluorescent (TADF) emitters are capable of pushing 75% triplet excitons to emit via the reverse intersystem crossing (RISC) process, and theoretically the 100% internal quantum efficiency (IQE) can be achieved. However, the ultralong delayed lifetime usually leads to the serious fluorescence quenching in aggregate states. As a result, the luminescent efficiency is sharply compromised in OLEDs under high current density, which is called efficiency roll-off. , …”
mentioning
confidence: 99%